Making Android-Based Augmented Reality in Buffer Solution Practicum to Improve Students Multiple Representation Ability - Sari Sari; Nisrina Zulfa; Ferli Septi Irwansyah (Postgraduate, University of Mataram, 2023)
This study aimed to develop android-based augmented reality multiple representation in buffer solution practicum. The research wants to describe the appearance, analyze results of the validation test and feasibility test of android-based augmented reality in buffer solution practicum, which is named Augmented Reality of Buffer Experiment (ARBE). The research was conducted using the Design Based Research (DBR) method which consisted of the analysis and development stages. The subjects of this research were two lectures of chemistry education, one lecture of informatics engineering, one teacher of chemistry, for validation test and 31 high school students of eleventh grade of nature science program for feasibility test. This research use a validation test and feasibility test instruments. The display on ARBE present a practicum menu and also five other menus completes the practicum menu. The results of the validation tests obtained an average value of rcount 0.85 and was declared valid, while the feasibility test obtained an average percentage of 82.14% indicating that android-based augmented reality in the buffer solution practicum to improve student’s multiple representation abilities is very feasible to use as a learning medium for buffer solution material.